Novel views upon the treatment and prevention of contagious ecthyma (orf) infection in small ruminants: with emphasis upon the problem in greek sheep and goat production. - STAMPOULIS (Δ. ΣΤΑΜΠΟΥΛΗΣ) D.; GIADINIS (N.Δ. ΓΙΑΔΙΝΗΣ) N. D.; PAPANASTASSOPOULOU (Μ. ΠΑΠΑΝΑΣΤΑΣΟΠΟΥΛΟΥ) M.; KRITAS (Σ.Κ. ΚΡΗΤΑΣ) S. K. (Journal of the Hellenic Veterinary Medical Society, 2018)
Contagious ecthyma (orf) is a viral disease that affects mainly the young small ruminants, while the virus can be transmitted to other animal species, as well as humans. The disease in neonatal lambs and goat kids causes lesions around the mouth and the nostrils, while in serious cases it causes stomatitis. Mild cases are self-limited, but complications (i.e. bronchopneumonia) and high mortality can be observed in severe cases. Most studies focus on the prevention of this disease, using hygiene measures and vaccines. Immune mechanisms have also been studied for this purpose. During the last decade some trials have been conducted for the treatment of orf infections in small ruminants and humans by using anti-viral drugs. Despite the advantages of these anti-viral drugs (high efficacy, specificity and safety for the epithelia), these efforts were mostly ineffective and remained at the experimental level for the veterinary practice. The aim of the present paper is to review the use of vaccines for the prevention of orf infection in small ruminants and to report experimental therapeutic protocols that could be useful for the treatment of the disease in future. Also, the article emphasizes upon the special problems from this disease in Greek sheep and goat flocks.